Analisis Kontrol Aliran Fluida Bervikositas Tinggi dengan Sensor Flow YF-S201 pada Otomatisasi Dispenser Minyak Goreng - Hadi Supriyanto (P3M Politeknik Negeri Indramayu, 2021)
The purpose of Automation system on the Hygenist Automatic Frying Oil Dispenser making is to assist the frying oil sellers or suppliers in measuring the oil accurately and minimize the frying oil contamination. The dispenser is designed using pump and flowsensor to measure the frying oil pumped out. Electric valve or faucet is used to prevent contamination of the oil as the substitute of manual faucet. This study is focused on designing and making automation system on the frying oil dispenser, measuring time and volume accuracy of dispenser. Dispensers can be moved, capable of accommodating 50 Kg of oil and have a choice of two quantities; 500ml and 250ml. As a result, flowsensor reading shows the same average frequency of 25 Hz and 35 Hz for filling 250 mL oil and 500 mL respectively. Time consumption for pumping 250 mL and 500 mL oil out from the dispenser is 8.85 s and 15,3 s respectively. Using delay program, the oil pumped out for 250 mL and 500 mL target volume need 5.75 s and 12 s delay time.